Efficacy of chloroquine with primaquine for uncomplicated Plasmodium vivax malaria without G6PD testing in Northwest Ethiopia: a one-arm in vivo prospective therapeutic efficacy study - Eyob Getu; Abdissa Biruksew; Teferi Eshetu; Abdulhakim Abamecha; Dawit Getachew Assefa; Hussein Mohammed; Yonas Wuletaw; Geremew Tasew; Getachew Tollera; Mesay Hailu; Moges Kassa; Ashenafi Assefa; et al. (Malaria Journal)
Abstract Background The declining efficacy and widespread resistance to antimalarial drugs (AMD) pose significant challenges to global malaria control and elimination efforts. To enhance treatment efficacy, the World Health Organization (WHO) recommends the use of combination therapies. This study aimed to evaluate the therapeutic efficacy of chloroquine with primaquine (CQ–PQ) for the treatment of uncomplicated Plasmodium vivax malaria in the study area. Methods The study utilized a single-arm, 42-day follow-up design to assess the therapeutic efficacy and safety of a treatment regimen in Northwest Ethiopia. Participants, all diagnosed with uncomplicated vivax malaria, received a 3-day course of chloroquine (CQ) at 25 mg/kg, followed by a 14-day course of primaquine (PQ) at 0.25 mg/kg. Participants were monitored with follow-up visits on days 1, 2, 3, 7, 14, 21, 28, 35, and 42. Data were double-entered into a standard Excel sheet by the WHO and analysed using SPSS v.26. Statistical analyses included Kaplan–Meier survival analysis, t-tests, and ANOVA, with statistical significance set at p < 0.05. Results Of the 100 participants enrolled, 92% completed the study. The cumulative treatment success rate for CQ–PQ was 93.7% (95% CI 0.86–0.97) on day 42, with a 6.3% (95% CI 0.03–0.14) treatment failure rate. Asexual parasite clearance was rapid, with 97% achieving clearance by day 2 and full clearance by day 3 in all but one participant. Haemoglobin levels increased significantly from 12.3 g/dL at baseline to 13.5 g/dL by day 42, with 84.2% of mild anaemic patients and 85.7% of moderate anaemic patients showing recovery. Common adverse events included abdominal pain (8%) and diarrhea (5%), all of which resolved by day 7. Conclusion CQ–PQ therapy demonstrated high efficacy in clearing parasitaemia and improving haemoglobin levels in patients with vivax malaria. These results highlight the potential of CQ–PQ as an effective treatment option, with a favourable safety profile. Further studies are needed to explore long-term outcomes and the impact of this treatment on malaria control in different settings.